Economic Value Added (EVA) sebagai Alternatif untuk Menilai Kinerja Keuangan Perusahaan PT. Indofood Sukses Makmur Tbk Periode 2019-2023 - Masyhuri, Muhammad Ade; Putri, Hana Tamara (Universitas Batanghari Jambi, 2024)
The aim of this research is to evaluate the financial performance of PT. Indofood Sukses Makmur Tbk uses the concept of economic value added (EVA). The type of descriptive research and quantitative approach used in this research and PT's annual financial reports. Indofood Sukses Makmur Tbk as a secondary data source. The results of this research found that PT. Indofood Sukses Makmur Tbk during the observation period had quite strong financial performance, this is indicated by the EVA value > 0; meaning PT. Indofood Sukses Makmur Tbk is able to generate added economic value during the 2019-2023 period.